In pursuit of a hapax: divergent interpretations of the root s-k-t - Noll, Sonja (Journal of Jewish studies, 2020)
A shift occurred in the lexicographical tradition of the hapax legomenon הַסְכֵּת (Deut. 27:9) between the seventeenth and nineteenth centuries. The hiphil imperative had previously been understood to mean ‘listen’ or ‘pay attention’, a tradition reflected in the Targumim, Peshitta, Vulgate, Aquila and early dictionaries. With the introduction of Arabic cognate evidence into Hebrew dictionaries in the seventeenth century, however, the meaning ‘be silent’, from the Arabic cognate سكت, began to appear in entries for this root. Dictionaries also began to include the translation σιώπα, ‘be silent’, from the Greek Septuagint, and eventually the gloss ‘be silent’ replaced ‘listen’ in bilingual biblical Hebrew dictionaries. The difference in meaning is minor, but this case study serves to illustrate the striking influence of cognate scholarship on the development of biblical Hebrew dictionaries.